The Life and Times of Sir George Grey, K.C.B., Volume 2 - Rees, William Lee (Cambridge library collection. History of Oceania, 1892)
Published in 1892, this two-volume biography chronicles the remarkable life and career of Sir George Grey (1812–98), the 11th premier of New Zealand. William Lee Rees (1836–1912), lawyer, politician and well-known supporter of Grey, co-wrote this work with his daughter Lily, and the books outline how Grey became arguably the most influential figure during the European settlement of New Zealand in the nineteenth century. The volumes proceed chronologically and are organised by the main events in Grey's life. Volume 2 covers Grey's second governorships of Cape Colony and New Zealand, his engagement in English politics and his return to New Zealand in 1870. It concludes with an assessment of Grey's personal characteristics, successes and failures. In addition to recounting the incidents, adventures and achievements of Grey's life, Rees also conveys Grey's principles and aspirations, giving the reader an insight into the character of this servant of the empire